A Study of Classroom Interaction Analysis Using Flander's Interaction Analysis: Analyzing the Impact of Flander's Interaction Analysis on Classroom Dynamics (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Interaction Analysis is a tool used in the classroom to capture quantitative and qualitative aspects of verbal instructor behaviour. It captures the verbal behaviour of teachers and students as an observational device that is directly linked to the social-emotional environment of the classroom. Interaction Analysis (IA) theoretical assumptions are that verbal contact is prevalent in a typical classroom situation the teacher exerts a great deal of control on the student and the behaviour of the student is influenced to a great extent by this form of teacher behaviour seen. The ten-category structure of Flanders, which aims to categorise all the verbal actions to be found in this paper. The aim is to promote the implementation of FIAC in the educational process in schools, as the quantity and consistency of teacher-student interaction is a vital element of effective teaching and improved learning in the classroom.